Lanskap Modal Ventura Sebelum Dan Setelah Era Otoritas Jasa Keuangan - Exsa Nur Chika Amitha; Sri Harini Dwiyatmi (JURNAL USM LAW REVIEW, 2025)
This research aims to analyze the changes in the institutional landscape of Indonesian venture capital. The urgency of this research is that venture capital is no longer a financing institution to foster small businesses, changing to be more business-oriented by applying guarantees in the form of movable and immovable assets. The research method used is a normative legal research method. The statute approach and the conceptual approach were used. The novelty of this research is a comprehensive review of the venture capital regulation from 1973 to 2023, which has implications for changes in the genuine character of venture capital as a financial institution. Venture capital financing accompanied by collateral is more like an ordinary debt and receivables agreement, no longer pure venture capital financing based on equity participation and shared risk. There has been a change in the landscape of venture capital since the era of the Financial Services Authority. The aspect of coaching small businesses in the form of technical assistance has been lost.   Penelitian ini bertujuan menganalisis perubahan lanskap kelembagaan modal ventura Indonesia. Urgensi penelitian ini modal ventura tidak lagi sebagai Lembaga Pembiayaan untuk membina usaha kecil, berubah menjadi lebih berorientasi bisnis dengan menerapkan jaminan berupa aset bergerak maupun tidak bergerak. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konsep (conceptual approach). Kebaruan dari penelitian ini adalah pada telaah menyeluruh atas Pengaturan Modal Ventura dari tahun 1973 hingga tahun 2023, yang berimplikasi pada perubahan karakter hakiki Modal Ventura sebagai Lembaga Pembiayaan. Pembiayaan modal ventura yang disertai jaminan lebih menyerupai perjanjian utang piutang biasa, bukan lagi pembiayaan modal ventura murni yang berbasis penyertaan modal (equity) dan risiko bersama. Dengan demikian terdapat perubahan lanskap perubahan modal ventura sejak era Otoritas Jasa Keuangan. Aspek pembinaan terhadap usaha kecil dalam bentuk technical assistance menjadi hilang.